Acrylamide fragment inhibitors that induce unprecedented conformational distortions in enterovirus 71 3C and SARS-CoV-2 main protease - Bo Qin; Gregory B. Craven; Pengjiao Hou; Julian Chesti; Xinran Lu; Emma S. Child; Rhodri M.L. Morgan; Wenchao Niu; Lina Zhao; Alan Armstrong; David J. Mann; Sheng Cui (Elsevier, 2022)
RNA viruses are critically dependent upon virally encoded proteases to cleave the viral polyproteins into functional proteins. Many of these proteases exhibit a similar fold and contain an essential catalytic cysteine, offering the opportunity to inhibit these enzymes with electrophilic small molecules. Here we describe the successful application of quantitative irreversible tethering (qIT) to identify acrylamide fragments that target the active site cysteine of the 3C protease (3Cpro) of Enterovirus 71, the causative agent of hand, foot and mouth disease in humans, altering the substrate binding region. Further, we re-purpose these hits towards the main protease (Mpro) of SARS-CoV-2 which shares the 3C-like fold and a similar active site. The hit fragments covalently link to the catalytic cysteine of Mpro to inhibit its activity. We demonstrate that targeting the active site cysteine of Mpro can have profound allosteric effects, distorting secondary structures to disrupt the active dimeric unit.